Effect of relative content on mechanical properties of coir and Napier grass fibers reinforced hybrid polyester composites. (2020) - Karthi, S.; Sasikumar, K.S.K.; Sangeetha, R.K.; Saravanan, N.
Abstract: Composite materials have been employed major part in current era for its light weight, good stiffness, high specific strength and flexible nature. In this research, The hybrid composites of unsaturated polyester based Coir/Napier grass hybrid fiber are prepared. The hybrid composites were prepared in the following proportion of Coir/Napier grass 100:0, 75:25, 50:50, 25:75 and 0:100 ratios whereas overall fibre weight ratios were maintained at 0.4Wf . Coir/Napier grass fibers are united in the same matrix (unsaturated polyester) to prepare hybrid composites and the tensile, flexural and impact properties are studied experimentally. A significant improvement in tensile, flexural and impact properties of Coir/Napier grass fiber hybrid composites is found. The morphology of coir/Napier grass fiber hybrid composite was investigated using scanning electron microscope.